Marketing or Effectiveness? Community Police in Peru [¿Marketing O Efectividad? Policía Comunitaria en Perú] - Dammert-Guardia, L (Universidad del Zulia, 2019)
The present study, using qualitative methodologies including 20 participant observations in different police stations in Lima as well as 80 interviews with police and 10 with experts during the first semester of 2017, analyzes the case of the community outreach program in Peru. In conclusion the diffusion of the concept is driven by emulation or interest in symbolic characteristics rather than its implementation. The results provide new insights into the process of implementing initiatives related to police work, strengthen the perception that part of the political debate is based on mythology rather than evidence and confirms the challenges that are still pending to achieve true transformations in the relationship with community. © 2019, Universidad del Zulia. All rights reserved.